Early Detection of Peripheral Arterial Disease (PAD) by Ankle Brachial Index (ABI) Examination in Type 2 Diabetes Mellitus Patients - Muhammad Sahlan Zamaa; Renaldi M; Sitti Nurhadijah (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2022)
Diabetes mellitus is one of the most common health problems in Indonesia. This disease has various complications, including the occurrence of pheriperal arterial disesase (PAD). One method to detect PAD is to examine the ankle brachial index (ABI). This study aims to conduct early detection of PAD incidence in diabetes mellitus patients. This research is a descriptive study with a population of 5649 and a total sample of 104 respondents who were taken using accidental sampling method. Data was collected through visits to the respondent's house. ABI data were collected using 8 MHz vascular doppler. On the right leg, there were 13 respondents who experienced PAD (11 mild occlusion and 2 moderate occlusion), for the left leg there were 13 respondents who experienced PAD (8 mild occlusion and 5 moderate occlusion). PAD is one of the complications that can occur in patients with diabetes mellitus. Early detection of PAD is important, because most patients with PAD do not feel any symptoms. This is important to prevent diabetic ulcers in the patient's feet.